(untitled) (Community Based Medical Journal, 2026)
Early detection of asymptomatic renal disease in children is crucial for preventing long-term complications. School-based screening through urinalysis offers a practical approach for this purpose. A cross-sectional, descriptive study was conducted in Community-Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and December of 2019, to screen for asymptomatic renal disease among school children in Mymensingh, Bangladesh, using urinalysis and to determine the prevalence of urinary abnormalities. Apparently healthy children aged 6-11 years from two purposively selected schools were included. Those with a history of renal disease, acute or chronic illness, and menstruating girls were excluded. After obtaining ethical approval and informed consent, participants underwent chemical and microscopic urinalysis. Among 200 children screened (mean age 8.4±1.4 years, 54.5% male), urinary abnormalities were found in 9.5% (n=19). Proteinuria was the most common finding (5.5%), followed by pyuria (5.0%) and hematuria (3.0%). The prevalence of abnormalities increased significantly with age (p<0.05). A significant association was found with hypertension (p<0.05) and higher BMI (overweight/obese, p<0.05). No significant gender difference was observed. Presumptive diagnoses included urinary tract infection (2.0%), glomerulonephritis (1.0%), and renal stone (0.5%). A significant proportion of asymptomatic school children screened had urinary abnormalities suggestive of underlying renal disease. These findings underscore the value of routine school-based urinalysis screening programs for the early detection and management of renal disorders in children. CBMJ 2026 January: vol. 15 no. 01 P:110-116